Penegakan Hukum Tindak Pidana Pembunuhan Berencana terhadap Hakim - Tedy Arman; Didik Suhariyanto; Ismail Ismail (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Premeditated murder is a crime (moord), it could be said that this is ordinary murder, but the difference is that it was planned in advance. The crime of murder is an act or deed committed by a person against another person so that the act can cause the loss of a person's life, this type of criminal act is a crime against a person's life, namely primarily assault and murder, both types of murder crimes are always preceded by torture which is always appears to be a charge after a charge of murder relating to evidentiary circumstances The research method used is the Normative Juridical research type, in accordance with the objectives the author wants to achieve, the methodology in designing the thesis research uses two types of approaches, namely the Statutory Approach and the Conceptual Approach. The Statute Approach is an approach carried out by examining all laws with the concept of law. Legal System Proving Premeditated Murder Against Judges: If the murder as intended in Article 338 is carried out immediately when the intention arises, whereas the implementation of premeditated murder is postponed after the intention is established, in order to regulate the plan, the manner in which the murder will be carried out. Upholding Justice Against Premeditated Murder of Judges, the judge's legal considerations before a decision is taken so the fuel is the values, principles, concepts, appropriate theories and evidence and facts revealed at trial. So that the decisions are good and in accordance with the community's sense of justice.